Structural and elemental characterization of glass and ceramic particles for bone surgery - Sirkiä Saara V; Nakamura Miho; Qudsia Syeda; Siekkinen Minna; Smått Jan-Henrik; Peltonen Jouko; Heino Terhi J; Hupa Leena; Vallittu Pekka K (United States, 2022)
Abstract
Objective
Clinically used bioceramics have been characterized previously with different kinds of methods and comparison of results have proven to be difficult due to varieties of the material properties of interest. Therefore, in this study we compared clinically commonly used bioceramics of hydroxyapatite and carbonate apatite, two bioactive glasses 45S5 and S53P4, and alumina with respect of properties which according to the present knowledge are significant for bone biology.
Methods
Physicochemical properties of the materials were characterized by various methods. Attenuated Total Reflectance Fourier Transform Infrared (ATR-FTIR) was used to analyze the material vibrational features. X-ray Power Diffraction (XRD) was used to characterize the material crystal structure and scanning electron microscopy-energy-dispersive x-ray analysis (SEM-EDXA) was used to evaluate the morphology and size of the materials and to calculate their oxide content. The dissolution behavior of the materials, ion release and pH changes in Tris buffer in a continuous flow-through reaction for 24-hours were determined. The change of the surface of the bioactive glasses by interfacial reaction during the Tris immersion was examined and the thickness of the surface reaction layer of the materials was studied.
Results
SEM examination showed that the particle morphology of BG 45S5, BG S53P4 and alumina particle’s surface was smooth. The surface of HAP was porous, but also CAP showed some surface porosity. An increase in the pH of the immersion solution was observed especially for BG 45S5 and BG S53P4. HAP, CAP and alumina caused only a minor increase in pH. BGs 45S5 and S53P4 showed a rapid initial release of sodium and calcium ions, followed by the release of silicon species. Minor release of sodium ions was registered for HAP, CAP and alumina. Calcium ion release was low but constant over the experimental time while only a minor initial dissolution was measured for HAP.
Significance
The in vitro study showed differences in the materials’ properties, which are considered to be important for biological suitability and in clinical applications, such as materials tomography, ion release and pH changes.